2018
DOI: 10.1242/jeb.176917
|View full text |Cite
|
Sign up to set email alerts
|

Brain mitochondrial bioenergetics change with rapid and prolonged shifts in aggression in the honey bee, Apis mellifera

Abstract: Neuronal function demands high-level energy production, and as such, a decline in mitochondrial respiration characterizes brain injury and disease. A growing number of studies, however, link brain mitochondrial function to behavioral modulation in non-diseased contexts. In the honey bee, we show for the first time that an acute social interaction, which invokes an aggressive response, may also cause a rapid decline in brain mitochondrial bioenergetics. The degree and speed of this decline has only been previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 93 publications
(176 reference statements)
2
28
1
2
Order By: Relevance
“…In order to determine the relationship between biogenic amine signaling and neural energetic state with respect to aggression, we assess the brain mitochondrial response to alarm pheromone in a simple laboratory context. In doing so, we note a contradiction in the direction of the mitochondrial bioenergetics response compared to that observed in the field (Rittschof et al, ). We evaluate whether this disparity is a function of multimodal cue presence in the field versus lab, or a function of individual activity levels at the time of the assay.…”
Section: Introductioncontrasting
confidence: 83%
See 4 more Smart Citations
“…In order to determine the relationship between biogenic amine signaling and neural energetic state with respect to aggression, we assess the brain mitochondrial response to alarm pheromone in a simple laboratory context. In doing so, we note a contradiction in the direction of the mitochondrial bioenergetics response compared to that observed in the field (Rittschof et al, ). We evaluate whether this disparity is a function of multimodal cue presence in the field versus lab, or a function of individual activity levels at the time of the assay.…”
Section: Introductioncontrasting
confidence: 83%
“…The neural energetic state of neurons and glial cells, however, also alters signaling potential of neural circuits and responds to signaling events. Several studies have demonstrated that neural energetic state, described as the activity of metabolic pathways, including glycolysis and oxidative phosphorylation, predicts the outcome of social interactions (Hollis et al, ; van der Kooij et al, ; Li‐Byarlay, Rittschof, Massey, Pittendrigh, & Robinson, ; Rittschof, Vekaria, Palmer, & Sullivan, ), and is regulated by social experience (Alaux et al, ; Chandrasekaran et al, ; Dong et al, ; Li‐Byarlay et al, ; Rittschof et al, ). These studies observe such relationships at the whole brain level as well as in behavior‐relevant brain regions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations